Integrating Digital Transformation in Islamic Educational Institutions: Challenges and Opportunities for Sustainable Management - Muhammad Irsyad Baitussalam; Achmad Basofitrah (DAAR EL-IDARAH: Journal of Islamic Education Management, 2025)
Digital transformation has become an essential aspect of modern education, including in Islamic educational institutions. These institutions face the dual responsibility of adopting technological innovation while maintaining their spiritual and moral foundations. This study aims to explore the challenges and opportunities of integrating digital transformation for sustainable management in Islamic education. Using a qualitative approach, data were gathered through interviews, observations, and document analysis. The findings show that digital transformation offers opportunities such as wider access to education, more effective management, and improved collaboration among stakeholders. At the same time, it presents challenges including limited infrastructure, digital literacy gaps, financial constraints, and the need to align technology with Islamic values. The study highlights the importance of leadership in balancing innovation with faith-based principles, ensuring that digital transformation supports both institutional sustainability and the holistic development of learners.